Developing Pragmatic Learning on Hybrid Learning Model for Indonesian Language and Literature Education Students - Andiopenta Andiopenta; Akhyaruddin Akhyaruddin; Yusra D; Eddy Pahar Harahap (AL-ISHLAH: Jurnal Pendidikan, 2024)
Hybrid learning integrates online technological advancements with traditional interactive learning methods, aiming to enhance educational outcomes. This study focuses on developing a hybrid learning model tailored for pragmatic education using the Borg Gall development model.The research employed the Borg Gall 10-step RD model involving 30 participants from an Indonesian language education program. Data collection methods included observations, questionnaires, and tests, analyzed using statistical tools. Key steps in the development process were: needs analysis, design, initial and subsequent field testing, iterative revisions, and final implementation.Field testing revealed marked improvements in learning outcomes. The initial test phase showed an increase in average scores from 5.50 (pre-test) to 6.71 (post-test). Subsequent testing showed scores improving from 6.15 (pre-test) to 7.41 (post-test). Statistical analyses confirmed significant enhancements in learning motivation (t = 9.554), creativity (t = 9.897), and learning outcomes (t = 9.996), with t-count values surpassing the critical t-table value of 2.136.The findings highlight the efficacy of the hybrid learning model in improving pragmatic education outcomes. Significant gains in motivation and creativity suggest that the model effectively integrates online and traditional teaching methodologies to address diverse educational needs.This study underscores the potential of hybrid learning models, developed using a systematic approach, in fostering improved learning outcomes for pragmatic education. The significant pre- and post-test differences validate its application and effectiveness.